Dyslipidemia management among patients with high and very high cardiovascular risk in Indonesia: a multi-center registry - Sunanto Ng; Anwar Santoso; Renan Sukmawan; Erwinanto Erwinanto; Erika Adam; Dwita Rian Desandri; Rita Zahra; Sony Hilal Wicaksono; Magma Purnawan Putra; Teuku Heriansyah; Badai Bhatara Tiksnadi; Yusra Pintaningrum (The Indonesian Heart Association, 2025)
Background Indonesia, the world's largest archipelago, faces significant challenges in equitable healthcare delivery due to its geographical and infrastructural disparities. Atherosclerotic Cardiovascular Disease (ASCVD) remains the leading cause of mortality, with over 659,000 deaths recorded in 2019. Effective dyslipidemia management is crucial for preventing adverse ASCVD events. Unfortunately, the lack of implementation of an updated national lipid management registry might hinder optimal strategy for the adverse events. This study evaluated dyslipidemia cholesterol management practices among high- and very high-risk patients across the country. Methods The study recruited 322 patients from eight centers across six provinces in Indonesia between May 2022 and March 2023. Patients were stratified based on the ASCVD risk and followed over three visits. Baseline clinical characteristics, lipid profiles, and treatment regimens were analyzed. Descriptive statistics summarized continuous and categorical variables, and low-density lipoprotein cholesterol (LDL-C) achievement was assessed. Results Of the 322 patients, 98.8% were very high-risk, with only 4.9% achieving <55 mg/dL and 21.2% achieving <70 mg/dL. Moderate-intensity statins were the most prescribed (51.2%), followed by high-intensity (36.6%). LDL-C reduction was most pronounced in private insurance patients, achieving a mean LDL-C of 69.8 mg/dL at the third visit compared to 98.9 mg/dL in National Health Insurance (Jaminan Kesehatan Nasional/JKN) participants. Missed visit rates increased over time, with 57.5% of patients missing the third visit, predominantly among JKN participants and low-income groups. Conclusion Majority of the population failed to achieve the recommended target of LDL-C levels. Dyslipidemia management in Indonesia remains suboptimal, with disparities driven by socioeconomic factors. Improved policies addressing medication availability, national lipid registry establishment, and equitable healthcare access are essential to enhance lipid management and reduce the burden of ASCVD in Indonesia.